Beyond Talk, Beyond Sound: Emotional Expression and the Future of Mobile Connectivity - Harper, Richard; Hodges, Steve (Mobile Communication in Everyday Life: An Ethnographic View, 2006)
The chapters in this book are testament to the range of possibilities enabled by current communications technologies. Our own interest in this is reflected in articles and books that we have written that report on the use of various technologies, whether it be SMS (Harper et al., 2005) or fully duplex mobile telephony (Brown et al., 2001). In this chapter, we want to take a different view: a view not on what communication technologies have done and do, but a view on what they might do when designed in novel ways. More particularly, in this chapter, we would like to explain why it is that, in the Socio-Digital Systems Group in Microsoft Research in Cambridge, England, we have set up a programme of inquiries into what we are calling New Communications Genre. This is a long-term programme where we hope to invent and demonstrate the value of a variety of new ways of communicating, of expressing and being in touch.